Superionic Fluorinated Halide Solid Electrolytes for Highly Stable Li‐Metal in All‐Solid‐State Li Batteries. Issue 36 (4th August 2021) - Yu, Tianwei; Liang, Jianwen; Luo, Liang; Wang, Limin; Zhao, Feipeng; Xu, Guofeng; Bai, Xiangtao; Yang, Rong; Zhao, Shangqian; Wang, Jiantao; Yu, Jinqiu; Sun, Xueliang
Abstract: The halide solid‐state electrolytes (SSEs) have received significant attention due to their high ionic conductivity and desirable compatibility with cathode materials. However, the reduction potential of the halide is still >0.6 V (versus Li/Li + ). Reduction stability is still one of the challenges that need to be addressed. The fluorides have a wide electrochemical stability window due to the large electronegativity of F – . In contrast, Li3 YBr6 (LYB) bromides have a narrower electrochemical window, although they have high lithium ion conductivity (>10 –3 S cm –1 ). Herein, a fluorine doping strategy is employed. The interfacial stability between fluoride‐doped bromides and lithium metal is researched by cycling of lithium symmetric cells. Li plating/stripping can maintain over 1000 h at 0.75 mA cm –2 . Interfacial protection mechanisms investigated by X‐ray photoelectron spectroscopy. A fluoride‐rich interfacial layer is formed in situ during the cycle, which achieves inhibition of the reduction. The Li metal treated fluorine doping of LYB exhibits significant potential in full cells. In fact, the induction of a stable in situ interfacial layer by fluorine doping can effectively improve the interfacial stability of bromides to lithium metal. Fluorine‐doped modification offers a new attempt to realize lithium metal applications in all‐solid‐state lithium batteries. Abstract : A fluoride‐rich interfacial layer is formed in situ during the cycle of an all‐solid‐state lithium battery, which achieves inhibition of unwanted reduction. The formation of in situ fluorinated layers in the cycling process enables higher contact areas and uniform distribution, which contributes to high cycle stability. The stable interfacial layer by fluorine doping can effectively improve the interfacial stability of bromides to lithium metal.